2017
DOI: 10.1021/acs.joc.7b00011
|View full text |Cite
|
Sign up to set email alerts
|

Tandem C–N Bond Formation through Condensation and Metal-Free N-Arylation: Protocol for Synthesizing Diverse Functionalized Quinoxalines

Abstract: Diverse functionalized quinoxalines were synthesized in good yields from arylamines and readily available β-keto oximes through condensation and metal-free N-arylation. The reaction was compatible with various functional groups, such as halides, cyano, and esters. A mechanism was proposed based on the experimental results. These quinoxalines were easily obtained on a gram scale and converted to various useful scaffolds. Compound LASSBio-1022 was prepared in 83% yield in two steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The synthetic route to QCA‐ d 4 and MQCA‐ d 4 is shown in Scheme . The synthesis strategy follows a recently published method by condensing β‐keto oximes with aryl amines, and the resulting N ‐aryl keto oximes were converted to quinoxalines through Lewis acid–mediated intramolecular N ‐arylation . First of all, commercially cheap aniline‐ d 5 was used as the starting material, and reacted with ethyl‐2‐(hydroxyimino)‐3‐oxobutanoate ( 1 ) or 2‐oxopropanal oxime using acetic acid and POCl 3 as catalysts, thus obtaining ethyl 3‐methylquinoxaline‐2‐carboxylate‐ d 4 ( 2 ) and 2‐methylquinoxaline‐ d 4 ( 3 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthetic route to QCA‐ d 4 and MQCA‐ d 4 is shown in Scheme . The synthesis strategy follows a recently published method by condensing β‐keto oximes with aryl amines, and the resulting N ‐aryl keto oximes were converted to quinoxalines through Lewis acid–mediated intramolecular N ‐arylation . First of all, commercially cheap aniline‐ d 5 was used as the starting material, and reacted with ethyl‐2‐(hydroxyimino)‐3‐oxobutanoate ( 1 ) or 2‐oxopropanal oxime using acetic acid and POCl 3 as catalysts, thus obtaining ethyl 3‐methylquinoxaline‐2‐carboxylate‐ d 4 ( 2 ) and 2‐methylquinoxaline‐ d 4 ( 3 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis strategy follows a recently published method by condensing β-keto oximes with aryl amines, and the resulting N-aryl keto oximes were converted to quinoxalines through Lewis acid-mediated intramolecular N-arylation. 8 First of all, commercially cheap aniline-d 5 was used as the starting material, and reacted with ethyl-2-(hydroxyimino)-3-oxobutanoate (1) or 2-oxopropanal oxime using acetic acid and POCl 3 as catalysts, thus obtaining ethyl 3-methylquinoxaline-2-carboxylate-d 4 (2) and 2-methylquinoxaline-d 4 (3), respectively. According to Jiao et al, 8 the authors reported that the oximes used in this type of quinoxaline synthesis must contain electron-withdrawing (EWG) group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations